2022
DOI: 10.1186/s13047-022-00540-9
|View full text |Cite
|
Sign up to set email alerts
|

First metatarsophalangeal joint arthrodesis/fusion: a systematic review of modern fixation techniques

Abstract: Background First metatarsophalangeal joint arthrodesis is commonly performed for symptomatic end-stage hallux rigidus. It has been postulated to produce good results in the literature. Various fixation techniques offer differences in union rates, complications and functional outcomes, stirring debates about which produces the best outcomes for patients. Therefore, this review aims to synthesise and compare the outcomes of modern fixation techniques used for first metatarsophalangeal joint (FMPJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 69 publications
(93 reference statements)
1
9
1
1
Order By: Relevance
“…This systematic review found a non-union percentage for moderate-to-severe hallux valgus of 7.7%, based on studies of overall medium quality. The results were higher than the 4.3-6.5% seen in other systematic reviews of first MTPJ arthrodesis due to hallux rigidus or hallux valgus combined (7,17,41). These findings are in line with our hypothesis that the difference in pathogenesis might explain this difference in non-union frequency.…”
Section: Discussionsupporting
confidence: 83%
“…This systematic review found a non-union percentage for moderate-to-severe hallux valgus of 7.7%, based on studies of overall medium quality. The results were higher than the 4.3-6.5% seen in other systematic reviews of first MTPJ arthrodesis due to hallux rigidus or hallux valgus combined (7,17,41). These findings are in line with our hypothesis that the difference in pathogenesis might explain this difference in non-union frequency.…”
Section: Discussionsupporting
confidence: 83%
“…During the last decades several types of plate fixation systems have been available to use fusing the FMTPJ. Several authors have declared that plating techniques are superior to other fixation techniques including patient-reported outcome, union rate, early ambulation, and reduced complication incidence [36][37][38][39][40] . It is important to find out if this specific internal fixation technique significantly can reduce the cost of health services and increase the patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Either the cheilectomy or the MTP arthrodesis, focus on these factors and does not prevent the disease recurrence. The osteotomy presented decompresses the joint and improves the anatomical situation of the first metatarsal, trying to avoid this recurrence (13,14) .…”
Section: Discussionmentioning
confidence: 99%